Synthesis and characterisation of poly(hydroxamic acid and amidoxime) grafted sago starch cheating resin for extraction of some metal ions - Tan, Boon Teong (2010)
Sago starch (AGU, anhydro glucose unit) was used to prepared a poly(hydroxamic acid-amidoxime) chelating resin. Methyl acrylate (MA) and acrylonitrile (AN) were firstly graft copolymerized onto sago starch by using a free radical initiating process in which eerie ammonium nitrate was used as an initiator. The percentage of grafting was significantly dependent upon the concentration d mineral add (H₂SO₄), eerie ammonium nitrate (CAN), MA, AN, as well as the reaction temperature and period. The highest yield was obtained when the concentrations of H₂SO₄, CAN, AN and MA were used at 0.7090 mol/L. 4 x 10⁻³) moI/L, 0.6016 mol/L and 0.4392 moI/L, respectively. The optimum temperature and reaction period were 50⁰C and 90 min, respectively. The conversion of ester and nitrile groups of the poIy(methyl acrylate-co-acrylonitrile) (PMA-co-AN) grafted AGU Into hydroxamie acid and amidoxime functional groups was then prepared via treatment of hydroxylamine under alkaline solution. The optimum poly(hydroxamic acidamidoxime) (PHA-PA) chelating resin was obtained when concentration of hydroxylamine hydrochloride was used at 0.8634 mol/L; reaction temperature at 75⁰C; 2 hours of reaction period; while the varying pH value was pH 13. The optimization of the PHA-PA chelating resin was evaluated by measured the sorption capacity of the resin towards copper metal ion with batch method. The PMA-co-AN grafted AGU and PHA-PA were characterized by FT-IR spectroscopy. The chelating behavior of the prepared resin towards cadmium, chromium, copper and zinc metal ions were investigated by using batch method. The binding capacities of the optimum chelating resin towards these metal ions were observed and it exhibited high sorption capacity for copper which observed at 3.576 mmol/g, at pH 6 after 24 hours of reaction period. The maximum binding capacities of the optimum chelating resin towards cadmium, chromium and zinc metal ions were observed at l.585 mmol/g, 1.658 mmol/g and 1.817 mmol/g, respectively; at pH 6 after 24 hours of reaction period. The optimum resin obtained also showed that it was capable to form a chelate complex when reacted with metal ions in trace level.